(untitled) (CIPEEX, 2022)
AGING IS A UNIVERSAL, INEVITABLE AND INHERENT PROCESS OF THE HUMAN CONDITION. IN TURN, THE ELDERLY ARE CLASSIFIED AS THOSE WHO ARE 65 OR OLDER IN DEVELOPED COUNTRIES, OR OLDER THAN 60 YEARS IN DEVELOPING COUNTRIES. OLD AGE ENCOMPASSES EXTRINSIC ASPECTS, SUCH AS PHOTOAGING, SMOKING AND FREE RADICALS, AND INTRINSIC ONES, SUCH AS MENOPAUSE, ANDROPAUSE AND SHORTENING OF TELOMERES, BEING THOSE PORTRAYED IN THIS WORK. IN ADDITION TO THESE ASPECTS, IT IS WORTH MENTIONING THE PROCESS OF ACCEPTANCE OF AGING INDIVIDUALLY FOR EACH ELDERLY PERSON. IN THE PRESENT STUDY, ACCEPTANCE WAS RELATED TO THE FOLLOWING VARIABLES: QUALITY OF LIFE, GENDER, FAMILY, SEXUALITY AND SPIRITUALITY. THEREFORE, THE OBJECTIVE OF THE ARTICLE IS TO ANALYZE THE EXTRINSIC AND INTRINSIC FACTORS AND THE PROCESS OF ACCEPTANCE OF AGING, AND THE GUIDING QUESTION FOR THE RESEARCH WAS "WHAT ARE SOME FACTORS RELATED TO AGING AND HOW IS IT ACCEPTED BY PEOPLE?". THE NATIONAL LIBRARY OF MEDICINE AND THE NATIONAL INSTITUTES OF HEALTH (PUBMED), THE ACADEMIC, THE SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND THE NATIONAL LIBRARY OF MEDICINE (MEDLINE), WITH THE SELECTION OF 21 ARTICLES IN THE ENGLISH OR PORTUGUESE LANGUAGE. IT WAS POSSIBLE TO OBSERVE THAT AGING IS THE RESULT OF A MULTIFACTORIAL DYNAMICS, WHICH REQUIRES ACCEPTANCE AND STILL LACKS COMPLEMENTARY STUDIES.